My Family Medical History and Me: Feasibility Results of a Cardiovascular Risk Reduction Intervention. Issue 3 (19th May 2014) - Imes, Christopher C.; Lewis, Frances M.; Austin, Melissa A.; Dougherty, Cynthia M.
Abstract Objective Evaluate the feasibility and acceptability of a behaviorally focused intervention designed to increase perceived cardiovascular disease (CVD) and coronary heart disease (CHD) risk in young adults with a family history (FH) of CVD/CHD. Design and Sample Single group, pre‐post‐test design. Fifteen, mostly female (n = 13, 86.7%), White, young adults (mean age 20.8 years) with a minimum of a high school education with a FH of CVD/CHD. Measures Feasibility examined the recruitment strategy, study procedures, appropriateness and quality of the study instruments, and problems that occurred during delivery of the intervention. Acceptability examined participants' engagement in the in person sessions and at home exercises and their feedback about the intervention. Intervention Two, in person sessions provided personalized, tailored messages about 10‐year and lifetime CHD risk based on risk factors, FH from a three‐generation pedigree, lipid levels, blood pressure, and smoking status, and brief counseling about how to engage in a healthy lifestyle to decrease CVD/CHD risk. Results The intervention was feasible and acceptable. Participants requested more information on healthy food choices, including which foods to avoid and which exercises most improve cardiovascular health. Conclusions Although requiring refinement, the intervention has potential public health implications and deserves further testing.